163 Endothelial Cell Derived Extracellular Vesicles Enriched with VCAM-1 in Inflammtion Stimulate Splenic Monocyte Migration. (3rd June 2016) - Akbar, Naveed; Digby, Janet; Cahill, Thomas J; Gardner, Laurienne; Rawlings, Nadiia; Johnson, Errin; McNeil, Eileen; Dragovic, Rebecca; Anthony, Daniel; Greaves, David; Choudhury, Robin P
Abstract : Background: In acute myocardial infarction (MI), monocytes are rapidly mobilised from the spleen to peripheral blood, from where they infiltrate injured tissue, with potential to contribute to both injury and repair. The mechanism by which the injured myocardium signals splenic-monocyte mobilisation remains poorly understood. Recent work shows extracellular vesicles (EV, which carry proteins, microRNA/mRNA) are a means of rapid cell-to-cell communication, which, combined with knowledge of their composition and propensity to be taken up by other cells, suggests a possible role in signalling. Here we show that acute MI results in a net increase in circulating endothelial cell (EC)-EV that induce splenic monocyte motility in vivo . Methods: MI was induced in mice. EV were isolated by ultra-centrifugation and analysed for size/number by Nanoparticle Tracking Analysis, western blot (EV-markers: Alix, TSG101, CD69, CD9 and Hsp70) and ELISA for EC markers (CD31, ICAM-1, P-selectin, E-selectin and VCAM-1). Primary cardiac mouse-EC (CM-EC) were used to produce EV in-vitro and were labelled fluorescently (PKH67) and transfected with cell-miR39-3p ( C.elegans ). EV were either tail vein injected into wild-type or CD68 GFP+ naïve mice and/or exposed to macrophages (RAW 264.7) in-vitro . Results: Acutely (24 hours) after MI there was a significant increase in circulating EV in mice (7.6 ± 1.7x10 8 /ml vs 3.6 ± 1.5 x 10 8 /ml, control, P < 0.01) that later subsided (4.6 ± 1.8 x 10 8 /ml 4th day post-MI). Plasma EV displayed EC-surface markers, suggesting EC origin. Pro-inflammatory TNF-α (3.0 ± 0.1 x 109/ml vs 1.5 ± 0.1x10 8 /ml control, P < 0.01) significantly increased EV production in CM-ECs in-vitro, whereas 'anti-inflammatory' IL-4 (1.3 ± 0.01 x 10 9 /ml) and IL-6 (1.5 ± 0.1 x 10 9 /ml) had no effect. Inflammatory-EC-EV displayed significant enrichment of VCAM-1 (P < 0.05). In-vitro there is a time-dependent accumulation of labelled EV in macrophages. Inflammatory-EC-EV significantly enhanced macrophage chemotaxis to MCP-1 in-vitro (2.2 ± 0.2 AU EV treated vs 1.7 ± 0.2AU untreated, P < 0.01), a response that was abolished by pre-incubating EC-EV with an anti-VCAM-1 antibody (1.8 ± 0.2AU, P < 0.05). Inflammatory EV significantly induced alterations in mRNA of motility genes by reducing PLEXIN-B2 (P < 0.001) and increasing ITGB2 (P < 0.001) expression in macrophages. Injected labelled EC-EV accumulate in the splenic red-pulp and injected inflammatory-EC-EV induced significant splenic monocyte mobilisation and peripheral monocytosis in-vivo in CD68 GFP+ naïve mice (P < 0.05). In conclusion: (1)  In vivo EV are released acutely after MI; (2) Plasma-EV protein composition is consistent with endothelial cell origin. (3) Injected EV localise to the spleen and(4) mobilise splenic monocytes. (5) In culture, EV increase cell motility and (6) regulate genes that are important in motility. These findings are all suggestive of a role for EC-derived EV in monocyte activation after acute MI.